Thoracic empyema: a 12-year study from a UK tertiary cardiothoracic referral centre. - Daniel J B Marks; Marie D Fisk; Chieh Y Koo; Menelaos Pavlou; Lorraine Peck; Simon F Lee; David Lawrence; M Bruce Macrae; A Peter R Wilson; Jeremy S Brown; Robert F Miller; Alimuddin I Zumla (PLoS ONE)
Background Empyema is an increasingly frequent clinical problem worldwide, and has substantial morbidity and mortality. Our objectives were to identify the clinical, surgical and microbiological features, and management outcomes, of empyema. Methods A retrospective observational study over 12 years (1999-2010) was carried out at The Heart Hospital, London, United Kingdom. Patients with empyema were identified by screening the hospital electronic 'Clinical Data Repository'. Demographics, clinical and microbiological characteristics, underlying risk factors, peri-operative blood tests, treatment and outcomes were identified. Univariable and multivariable statistical analyses were performed. Results Patients (n = 406) were predominantly male (74.1%); median age = 53 years (IQR = 37-69). Most empyema were community-acquired (87.4%) and right-sided (57.4%). Microbiological diagnosis was obtained in 229 (56.4%) patients, and included streptococci (16.3%), staphylococci (15.5%), gram-negative organisms (8.9%), anaerobes (5.7%), pseudomonads (4.4%) and mycobacteria (9.1%); 8.4% were polymicrobial. Most (68%) cases were managed by open thoracotomy and decortication. Video-assisted thoracoscopic surgery (VATS) reduced hospitalisation from 10 to seven days (P = 0.0005). All-cause complication rate was 25.1%, and 28 day mortality 5.7%. Predictors of early mortality included: older age (P = 0.006), major co-morbidity (P = 0.01), malnutrition (P = 0.001), elevated red cell distribution width (RDW, P<0.001) and serum alkaline phosphatase (P = 0.004), and reduced serum albumin (P = 0.01) and haemoglobin (P = 0.04). Conclusions Empyema remains an important cause of morbidity and hospital admissions. Microbiological diagnosis was only achieved in just over 50% of cases, and tuberculosis is a notable causative organism. Treatment of empyema with VATS may reduce duration of hospital stay. Raised RDW appears to associate with early mortality.